An Analysis regular verb Vocabulary Mastery in recount Texts of Grade 10 Students of SMA Teladan Pematangsiantar - Titin Marpaung; Selviana Napitupulu (Educate : Journal of Education and Learning, 2026)
This study analyzes the mastery of regular verb vocabulary in recount texts written by tenth-grade students of SMA Teladan Pematangsiantar. Employing a descriptive mixed-methods approach, the research involved 39 students selected through purposive sampling. Data were collected using a writing test as the main instrument, supported by classroom observation and a questionnaire. Students were asked to write recount texts based on their personal experiences, and the regular verbs used were analyzed for accuracy. The findings reveal that students’ mastery of regular verbs is generally high, with a mean score of 88.03, categorized as Excellent. Most students demonstrated accurate use of regular verb forms, although some errors were still evident. The results also indicate that students’ difficulties are influenced by limited practice and first language interference. Overall, the study shows that while students have a strong understanding of regular verb usage in recount texts, continued instructional support is necessary to enhance grammatical accuracy. Pedagogically, the findings suggest that explicit instruction combined with focused practice and corrective feedback can further strengthen students’ mastery of regular verbs in EFL writing contexts.